EXPLORING LINGUISTIC UNIVERSALS AND TYPOLOGICAL PATTERNS: AN ANALYSIS OF THE COGNITIVE AND CULTURAL FACTORS THAT SHAPE LANGUAGE STRUCTURES ACROSS DIVERSE LANGUAGES - Satibaldiev Erkinjon Kamilovich (American Journals, 2023)
This article discusses linguistic universals and typological patterns, which have been studied in the field of linguistics for many years, and highlights the need for further research in this area. The article provides an overview of previous research on linguistic universals and typological patterns, identifies gaps in the literature, and discusses the cognitive and cultural factors that shape language structure. The study aims to analyze the syntactic structures of English and Russian, compare the similarities and differences between them, and identify linguistic universals and typological patterns across languages. The analysis of the syntactic structures of English and Russian reveals several similarities and differences between the two languages, such as word order patterns, the use of auxiliary verbs and prepositions, and the reliance on inflectional morphology. The study's findings contribute to our understanding of the underlying cognitive and cultural factors that shape language structures and have significant implications for linguistic typology and universals.
Keywords: linguistic universals; typological patterns; language structure; word order patterns; morphological patterns; cognitive factors; cultural factors; syntactic structures